2022
DOI: 10.3390/su141610276
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Consumer Behavior during the COVID-19 Pandemic: A Comparative Analysis between Polish and Turkish Consumers

Abstract: Undoubtedly, the COVID-19 pandemic has left an indelible mark on every aspect of human life, and, perhaps most significantly, on the operation of the world’s economy. Restrictions and limitations on freedom of movement had a clear impact on the ways in which companies and households functioned, and consumer behaviors and purchasing habits were demonstrably influenced in turn. Thus, the aim of this article is to illustrate these changes in light of the pandemic and, moreover, to highlight the related challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… Crosta et al (2021) found that changes in spending levels were associated with changes in consumer behavior, with necessities being predicted by anxiety and COVID-related fear, and non-necessities being predicted by depression. Bareja-Wawryszuk et al (2022) found that there were clear differences in the nature of changes in consumer behavior between respondents from Turkey and Poland, with the purchasing habits of respondents in Turkey changing to a greater extent. Argyropoulou et al (2023) found that the pandemic has impacted various aspects of consumer behavior in Greece, with online shopping and social media usage increasing during this period.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 95%
“… Crosta et al (2021) found that changes in spending levels were associated with changes in consumer behavior, with necessities being predicted by anxiety and COVID-related fear, and non-necessities being predicted by depression. Bareja-Wawryszuk et al (2022) found that there were clear differences in the nature of changes in consumer behavior between respondents from Turkey and Poland, with the purchasing habits of respondents in Turkey changing to a greater extent. Argyropoulou et al (2023) found that the pandemic has impacted various aspects of consumer behavior in Greece, with online shopping and social media usage increasing during this period.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 95%